Construção de banco de questões para exames de proficiência em inglês para programas de pós-graduação - Monzón, Andrea Jessica Borges (Universidade Federal de São Carlos, 2008)
As English is the most frequent language in science and in the academic community, the proficiency in this language is necessary to whom is in this environment included, mainly regarding reading comprehension. Many proficiency exams that evaluate this ability in candidates or graduate students, although request students only to translate a text. At ICMC (USP - São Carlos) since 2001 an English Proficiency Exam (EPE) has been made evaluating graduate students knowledge of research article as a genre (Swales,1990; Weissberg & Buker, 1990). The assessment is divided into four modules: 1) linguistic conventions, 2) structure of research article, 3) reading comprehension and 4) writing strategies which are peculiar to Academic English (Aluísio et al, 2003). However, the modules are not fully implemented and there s still a lot of space for linguistic reflections, once the exam was elaborated by a professor in the Computer Science area. The current study aims the construction of a corpus and the elaboration of questions referring to module 1 with the axioms needed in any evaluation (Perrenoud, 1999; Miller et al, 1998), the peculiar characterists of a foreign language test, Bloom s Taxonomy (1984), the Admissible Probability Method (APM) (Klinger, 1997) and the most recurrent mistakes made by Brazilian graduate students (Genoves Jr. et al, 2007). Computer tools will be used, such as: a concord and a word list that are commonly available in corpus processor like WordSmith Tool besides a chunker, a parser and a parser tree. The questions will be part of an item base to be used for: 1) the elaboration of future EPEs; 2) raising relevant information about the conditions of the testees reading comprehension; and 3) testees´ study and preparation through CALEAP-Web (Gonçalves, 2004).
Keywords: Língua estrangeira - avaliação; Proficiência; Avaliação automática; Gênero textual; Avaliação em LE; Foreign language evaluation; Proficiency exam; Automatic evaluation; Academic genre; LINGUISTICA, LETRAS E ARTES::LINGUISTICA